Phonological and executive working memory in L2 task-based speech planning and performance. Issue 4 (1st October 2016) - Wen, Zhisheng (Edward)
Abstract : The present study sets out to explore the distinctive roles played by two working memory (WM) components in various aspects of L2 task-based speech planning and performance. A group of 40 post-intermediate proficiency level Chinese EFL learners took part in the empirical study. Following the tenets and basic principles of the Phonological/Executive (P/E) Hypothesis [i.e. the P/E model, Wen, Z. 2015. Working memory in second language acquisition and processing: the phonological/executive model. In Working Memory in Second Language Acquisition and Processing, ed. Z. Wen, M. Mota and A. Mcneill, 41–62. Bristol, UK: Multilingual Matters; Wen, Z. 2016. Working Memory and Second Language Learning: Towards an Integrated Approach . Bristol, UK: Multilingual Matters], WM was conceptualised as consisting of phonological working memory (PWM) and executive working memory (EWM), measured respectively by a non-word repetition span task and speaking span tasks in participants' L1 Chinese and L2 English. Their L2 speech performance on video-clip narrative tasks was analysed and coded in terms of a series of fluency, accuracy, complexity and formality measures. Statistical analyses indicate that although participants' PWM was not related to any of the speech performance measures, their EWM was significantly correlated with some lexical, syntactic and stylistic features of L2 speech performance. These results and findings are discussed in relation to the hypotheses laid out in the P/E model as well as their implications for future L2 task planning research.